The Education Systems of Europe
VIII, 879 p.
Keywords: This book is the first to present an analytical description of the education systems of all European countries, following common guidelines. These conceptual guidelines consider various criteria concerning presumptions as to the quality of a good education system. One of the book’s central aims is to explore the paradoxical character of education, i.e. the relationship between universal values and the search for a national identity. It looks at the dynamics of the developments in the ‘new’ Eastern European countries compared to those of ‘older’ Western European countries. It then goes on to discover a common pattern of European education and compares it to that of education systems outside Europe, making it relevant reading to educators around the world. The handbook provides many suggestions for further study.